Evolution of electrons’ distribution function during their interactoin with plasma: numerical simulation - Anisimov, I.O.; Levitsky, S.M.; Sasyuk, D.V.; Siversky, T.V. (Вопросы атомной науки и техники, 2003)
One-dimension numerical simulation of the beam-plasma system was carried out using the big-particles-in-cells method. Instantaneous velocity distribution of the beam electrons depending of the distance from injector was received. The distribution function was found to be oscillating and strongly irregular. This result corresponds with the data of the previous calculations and laboratory experiments. After averaging over the sufficiently long time interval the distribution function becomes smoothed and similar to a plateau that was observed in the laboratory experiments.